ISOLASI SITRONELLAL DARI MINYAK SEREH WANGI (Cymbopogon winterianus Jowit) DENGAN DISTILASI FRAKSINASI PENGURANGAN TEKANAN - Lucia Wiwid Wijayanti (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2015)
Abstract: It has been carried out the isolation of citronellal from citronella oil by fractinational distillation under reduced pressure. From 500 g citronella oil, citronellal has been received at the amount of 10 g with the purity of 81.30%, 210 g with the purity of 99.14%. Keywords: isolation of citronellal, citronella oil, fractional distillation under reduced pressure